2019
DOI: 10.31744/einstein_journal/2019ao4436
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of G6PD deficiency and molecular characterization of G202A, A376G and C563T polymorphisms in newborns in Southeastern Brazil

Abstract: Objective To evaluate the prevalence of G6PD deficiency and characterize G202A, A376G and C563T polymorphisms in neonates using molecular assays. Methods A total of one thousand samples were tested through quantitative analysis of enzyme activity, detecting 25 G6PD-deficient individuals. Patients identified as deficient were submitted to molecular analysis quantitative real-time polymerase chain reaction – (qPCR) to investigate the presence of variants associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
0
0
1
Order By: Relevance
“…The mean G-6-PD activity of 2.50 found in the present study is below the normal range (6.97 to 20.5 U/g Hb) indicated by the manufacturer of the test kit used (Randox Kits). These findings corroborates with studies reported by Ondei et al 37 and Pereira et al 38 in Brazil, in Kenya by Shah et al 39 and in Venezuala (America) by Vizzi et al 40 . This significantly lower G-6-PD activity in the test subjects is not unexpected as G-6-PD activity have been accepted as an indication for deficiency that has been implicated in the pathogenesis for many disease such as diabetes angiopathy, hypertension, retinopathy, cardiac dysfunction in people living with G-6-PD deficiency 41 .…”
Section: Discussionsupporting
confidence: 92%
“…The mean G-6-PD activity of 2.50 found in the present study is below the normal range (6.97 to 20.5 U/g Hb) indicated by the manufacturer of the test kit used (Randox Kits). These findings corroborates with studies reported by Ondei et al 37 and Pereira et al 38 in Brazil, in Kenya by Shah et al 39 and in Venezuala (America) by Vizzi et al 40 . This significantly lower G-6-PD activity in the test subjects is not unexpected as G-6-PD activity have been accepted as an indication for deficiency that has been implicated in the pathogenesis for many disease such as diabetes angiopathy, hypertension, retinopathy, cardiac dysfunction in people living with G-6-PD deficiency 41 .…”
Section: Discussionsupporting
confidence: 92%
“…O tema abordado neste estudo foi planejado mediante a necessidade de abordar um assunto pouco conhecido, que é a deficiência de glicose 6 fosfato desidrogenase (G6PD), mais que acomete grande parte da população e não é diagnosticada precocemente, já que na maioria dos casos são assintomáticos, e estão relacionados ao metabolismo do eritrócito e suas variantes a nível genético da enzima. Para Pereira et al (2019), evidenciou que a maioria dos pacientes com deficiência de G6PD são assintomáticos e que desenvolvem crises hemolíticas ao serem expostas a estresses oxidativos como infecções, uso de drogas e alguns alimentos, e predominantemente acometem o sexo masculino, por ser uma enzimopatia que afeta o cromossomo X, daí a importância da triagem neonatal para identificação precoce e encaminhamento para a realização do tratamento correto. Diante disso, Silva et al (2022), evidenciou que o diagnóstico precoce de qualquer doença faz a diferença na qualidade de vida e na eficácia do tratamento, e na deficiência de G6PD o diagnóstico pode ser feito por meio do teste do pezinho, sendo considerada uma doença rara, porém em neonatos desenvolve icterícia nas primeiras 24 horas de vida ou apresenta níveis alto de bilirrubinemia o que provocará palidez, icterícia, fadiga, esplenomegalia e urina escura, o que é necessário a adoção do tratamento imediatamente para evitar complicações mais graves.…”
Section: Resultsunclassified